2017
DOI: 10.5897/ajar2016.11705
|View full text |Cite
|
Sign up to set email alerts
|

Combining ability analysis of quality protein maize (QPM) inbred lines for grain yield, agronomic traits and reaction to grey leaf spot in mid-altitude areas of Ethiopia

Abstract: A study was carried out to study the combining ability effects of diallel cross hybrids for grain yield, agronomic traits and reaction to grey leaf spot (GLS). Forty five experimental diallel cross hybrids made from ten quality protein maize (QPM) inbred lines with varying level of resistance to GLS were evaluated along with three checks at Bako and Jima Research Centers during 2014/2015 cropping season. Analysis of variance showed significant variation (P≤0.05) among genotypes and between environments. This d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…In agreement with this finding, significant mean square due to genotypes for grain yield and yield related traits in maize were also reported by previous investigators [31,15,53,10,21,4] .…”
Section: Resultssupporting
confidence: 91%
“…In agreement with this finding, significant mean square due to genotypes for grain yield and yield related traits in maize were also reported by previous investigators [31,15,53,10,21,4] .…”
Section: Resultssupporting
confidence: 91%
“…The negative significant GCA effect has a tendency to reduce plant height whereas the positive significant has a trend to increase plant height in the crosses of offspring. These findings had resembled results with the preceding study of various authors (Matin et al, 2016;Bitew et al, 2017 andMelkamu et al,2020). In the same way, T1 (positive), T3 and T4 indicated positive and negative significant GCA effects for plant height whereas T1 and T3 showed significant GCA effects for EH to across locations (Table -3).…”
Section: General Combining Ability Effect Estimatessupporting
confidence: 91%
“…In line with this study, many maize researchers also have reported significant differences in GCA for grain yield and yield-related traits in different maize genotypes studied. Legesse et al (2017), Tolera et al (2017), Bitew et al (2017) and Gemechu et al (2020) in separate study suggested that both GCA and SCA effects are significant and important for grain yield and most other traits studied.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The current results are in line with the findings [37]; [38]; [39]; [25]; [40]; [13]; [26] and [41].The higher grain yield records were obtained from the crosses of L1 x L4 (11.79 ton ha -1 ), L2 x L4 (10.67 ton ha -1 ), L1 x L5 (10.42 ton ha -1 ), L7 x L8 (10.20 ton ha -1 ) L4 x L6 (10.1 ton ha -1 ) as compared to best performing check BH546 (9.93 ton ha -1 ) (Table 3) indicating that the two combined inbred lines in each crosses might be genetically diverse or belong to different heterotic groups. [42]and [43] reported that the performance of maize hybrids for grain yield greatly depends on the level of heterosis expressed in their hybrids and can be maximized by crossing inbred lines belonging to different heterotic groups. Contrarily, the lowest grain yield was recorded from the crosses of L8 x L10 (5.84 ton ha -1 ) indicating that the two inbred lines are genetically similar or belonging to same heterotic groups.…”
Section: Discussionmentioning
confidence: 99%